2015
DOI: 10.1016/j.jdent.2015.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of fluoride and sodium hexametaphosphate in toothpaste on enamel demineralization in situ

Abstract: This dentifrice could be a viable alternative to patients at high risk of caries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 30 publications
4
18
0
Order By: Relevance
“…(38,39) Also, the antimicrobial action of SHMP is related to its capacity to increase the permeability of the bacteria and glucose transport when it links to the Mg+ present in the outer membrane. (40) These results were in agreement with an in vitro study carried out by Post et al (41) in which the influence of SHMP on selected bacteria was assessed. The results showed that most Gram-positive bacteria were prevented from growing on medium containing 0.1 % SHMP and Gram-negative bacteria were capable of growing in higher concentrations even up to 10 % SHMP.…”
Section: Discussionsupporting
confidence: 89%
“…(38,39) Also, the antimicrobial action of SHMP is related to its capacity to increase the permeability of the bacteria and glucose transport when it links to the Mg+ present in the outer membrane. (40) These results were in agreement with an in vitro study carried out by Post et al (41) in which the influence of SHMP on selected bacteria was assessed. The results showed that most Gram-positive bacteria were prevented from growing on medium containing 0.1 % SHMP and Gram-negative bacteria were capable of growing in higher concentrations even up to 10 % SHMP.…”
Section: Discussionsupporting
confidence: 89%
“…As dental caries is the most common chronic oral disease worldwide (Clarkson, Watt, & Rugg-Gunn, 2010), enhancing the ability of fluoridated products against mineral loss can potentially improve its effect against dental caries. Sodium hexametaphosphate (HMP) is a cyclic inorganic phosphate (Kulaev, Vagabov, & Kulakovskaya, 2005, Ch. 1) that has been added to fluoride products as toothpastes (Camara, Miyasaki, Danelon, Sassaki, & Delbem, 2014;Camara et al, 2015Camara et al, , 2016 and gels (Conceição et al, 2015) with the purpose to increase the capacity of such products to reduce enamel demineralization and to enhance remineralization. The assumption would be that HMP would retain ionic species like CaF + and Ca 2+ , leading to a reticular formation of HMP-Ca 2+ layer on enamel, which in turn increases calcium availability during de-and re-mineralization processes (Camara et al, 2014(Camara et al, , 2016Conceição et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This effect is greater using the salt in its nano-sized form (∼87 and ∼78%, respectively, for ΔIHR and ΔIMR) when compared 1100F. To produce this effect, HMP facilitates the diffusion of ions calcium and phosphate into the enamel [da Camara et al, 2015], without any significant effect on enamel fluoride uptake, as previously mentioned. HMP is negatively charged cyclic phosphate that leads to larger amount of electron-donor sites on the enamel surface and, consequently, enhances the adsorption of ionic species as Ca 2+ , H 2 PO 4 -and CaH 2 PO 4 + [Neves et al, 2018], which are important in enhancing fluoride, calcium and phosphate diffusion into enamel.…”
Section: Discussionmentioning
confidence: 79%
“…As HMP associated to 1,100 ppm F did not enhance enamel F uptake [Dalpasquale et al, 2017;da Camara et al, 2015;da Camara et al, 2016], the superior results with nano-sized HMP is probably due to the higher reactivity of these particles [Dalpasquale et al, 2017]. Given that the anticaries effect of fluoride toothpastes (i.e., without HMP/HMPnano) is usually related to the ability to increase enamel fluoride concentrations, it can be concluded that the mechanism of action of HMP/ HMPnano containing fluoride toothpastes is somehow different from products containing fluoride only.…”
Section: Discussionmentioning
confidence: 99%